Species-Level Variability in Extracellular Production Rates of Reactive Oxygen Species by Diatoms - Schneider, Robin J.; Roe, Kelly L.; Hansel, Colleen M.; Voelker, Bettina M. (Frontiers in Chemistry, 2016)
Biological production and decay of the reactive oxygen species (ROS) hydrogen peroxide (H2O2) and superoxide (O2-) likely have significant effects on the cycling of trace metals and carbon in marine systems. In this study, extracellular production rates of H2O2 and O2- were determined for five species of marine diatoms in the presence and absence of light. Production of both ROS was measured in parallel by suspending cells on filters and measuring the ROS downstream using chemiluminescence probes. In addition, the ability of these organisms to break down O2- and H2O2 was examined by measuring recovery of O2- and H2O2 added to the influent medium. O2- production rates ranged from undetectable to 7.3 x 10-16 mol cell-1 hr-1, while H2O2 production rates ranged from undetectable to 3.4 x 10-16 mol cell-1 hr-1. Results suggest that extracellular ROS production occurs through a variety of pathways even amongst organisms of the same genus. Thalassiosira spp. produced more O2- in light than dark, even when the organisms were killed, indicating that O2- is produced via a passive photochemical process on the cell surface. The ratio of H2O¬2 to O2- production rates was consistent with production of H2O2 solely through dismutation of O2- for T. oceanica, while T. pseudonana made much more H2O2 than O2 . T. weissflogii only produced H2O2 when stressed or killed. P. tricornutum cells did not make cell-associated ROS, but did secrete H2O2-producing substances into the growth medium. In all organisms, recovery rates for killed cultures (94-100% H2O2; 10-80% O2-) were consistently higher than those for live cultures (65-95% H2O2; 10-50% O2-). While recovery rates for killed cultures in H2O2 indicate that nearly all H2O2 was degraded by active cell processes, O2- decay appeared to occur via a combination of active and passive processes. Overall, this study shows that the rates and pathways for ROS production and decay vary greatly among diatom species, even between those that are closely related, and as a function of light conditions.